Factors of Traffic Demand - Perić, Teodor (Promet - Traffic&Transportation, 2012)
Traffic demand and supply are in mutual interaction andmutually coordinated.Transport needs (of goods and passengers) cause an increasein consumption, and on the other hand influence theconstruction and improvement of available traffic capacities,which in tum provides conditions for new increase in transportdemand. As a result, traffic acts in return on the development ofinduslly and also for the needs of people. It precedes the developmentof demand, i. e. its interaction provides the possibilityof increase in the tramport se1vice demand.